Cecal volvulus in children - Mohamed Oulad Saiad; Najoua Aballa (Wolters Kluwer Medknow Publications, 2021)
Cecal volvulus is a rare complication of malfixation anomalies and intestinal malrotation in children. Only few cases have been reported. The rarity of the condition, frequently leads to diagnostic delay and complications. The best option for cecal volvulus repair remains unclear. Our aim is to increase the awareness of surgeons about cecal volvulus and to discuss its management.